Bādhaḥ - Gaṅgeśa (Kendrīyasaṃskr̥tavidyāpītham ; Rāṣṭriyasaṃskr̥tasaṃsthānam, 1985)
Basic work, with commentary and supercommentary, of the neo-Nyaya school in Indic philosophy; portion of Tattvacintāmaṇi dealing with contradiction (bādha), one of the five forms of fallacious middle term (hetvābhāsa).